Novel Role of Enteral Monosaccharides in Intestinal Lipoprotein Production in Healthy Humans - Xiao, Changting; Dash, Satya; Morgantini, Cecilia; Lewis, Gary F. (Arteriosclerosis, thrombosis, and vascular biology, 2013)
OBJECTIVE—Overproduction of triglyceride-rich lipoproteins (TRLs) by liver and intestine contributes to hypertriglyceridemia and may increase cardiovascular risk. Dietary carbohydrates, especially fructose, have been shown to amplify postprandial lipemia but little is known about its effect on intestinal TRL particle production. Here, we examined intestinal and hepatic TRL particle production in response to enteral glucose or fructose in the presence of enteral lipid. APPROACH AND RESULTS—In 2 randomized studies, 4 to 6 weeks apart, 7 healthy male subjects received intraduodenal infusion of Intralipid plus saline or glucose. TRL-apolipoprotein (apo) B48 and apoB100 kinetics were assessed under pancreatic clamp conditions. In a separate study of another 7 subjects under similar conditions, glucose was replaced by fructose. When coinfused with Intralipid into the duodenum, glucose markedly stimulated TRL-apoB48 production (P<0.01), with a concomitant moderate increase in fractional clearance (P<0.05), resulting in net elevation of TRL-apoB48 concentration. TRL-apoB100 concentration, fractional clearance, and production were not significantly affected by glucose. When glucose was replaced by fructose, both TRL-apoB100 and apoB48 production (P<0.05), but not fractional clearance, were enhanced compared with Intralipid alone. CONCLUSIONS—These results reveal a novel role of monosaccharides in acutely enhancing intestinal lipoprotein particle production, thereby aggravating hyperlipidemia.